The Role of Media in Intellectual, Social and Economic Transformation (Journal of Asian Development Studies, 2024)
This research article explains the role of media from three perspectives. First, we describe intellectual growth in the context of how media contributes to the advancement of human thought, highlighting the direct relationship between intellectual evolution and human and cultural development. This implies that human development also depends on intellectual and mental evolution. Any civilization that has achieved high levels of progress has undoubtedly been supported by the efforts and roles of media behind the scenes. The second aspect discusses the social role of media. It is widely recognized that the stronger the social process of media, the more impactful the social message will be. Throughout history, society has only been able to achieve significant milestones when media has actively participated in the social process. Media has portrayed human living and lifestyle, which later became the foundation for emerging societies. This is a definitive aspect of the role of media in social change. The third role illustrates that there is no sector of the economy where media has not promoted human strategies. Whenever an economic plan is formulated, media supports those plans and successfully attracts consumers' mindsets toward the relevant projects. This research article is structured to elucidate these three aspects.